2005
DOI: 10.1002/anie.200500488
|View full text |Cite
|
Sign up to set email alerts
|

Mining the Tetraene Manifold: Total Synthesis of Complex Pyrones from Placobranchus ocellatus

Abstract: A natural product anticipated through total synthesis! Ocellapyrone A was obtained in the laboratory several months before the structure of this unusual natural product (see scheme) was reported. An isomerization/8π–6π electrocyclization cascade was used for the formation of the natural product from a polyene precursor. The synthesis of ocellapyrone B from a diastereomer of ocellapyrone A was also performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(45 citation statements)
references
References 23 publications
1
44
0
Order By: Relevance
“…Synthetic targets include, the heterocyclic core of GE 2270 [34], peridinin [35], pyrones isolated from placobranchus ocellatus [36], terpenepolyketide natural products [37], dihydroxerulic and xerulinic acid [38], bipinnatin J [39], elipticine [40], (+)-7-deoxytrans-dihydronarciclasine [41], gambierol [42], taiwaniaquinol [43], (−)-scabronine G [44], garsubellin A [45], piericidin A1 and B1 [46], lucilactaene [47], fostriecin [48], lupine alkaloids [49], ␤-C-glycosides [50], (+)-crocacin D [51], lobatamide analogs [52], epoxyquinoid compounds [53,54], (+)-SCH 351448 [55], 3-methyl-2,5-dihydro-1-benzoxepin carboxylic acids [56], (+)-ochromycinone and (+)-rubiginone B 2 [57], EI-1941-1 and EI-1941-2 [58], mycothiazole [59], 6 -epiperidinin [60], aureothin and N-acylaureothamine [61], cyercene A and placidenes [62], herbindole B [63], (+)-tubelactomicin A [64], saudin [65], peroxyacarnoates A and D [66], aureothin, N-acetylaureothamine, aureonitrile [67], elysiapyrones [68], altromycin B [69], (+)-phorboxazole A and analogues [70,71], (−)-SNF4435 C and (+)-SNF4435 D [72], A2E [73], paracentrone [74]<...>…”
Section: Carbon-carbon Bond-forming Reactions Via Transmetallationmentioning
confidence: 99%
“…Synthetic targets include, the heterocyclic core of GE 2270 [34], peridinin [35], pyrones isolated from placobranchus ocellatus [36], terpenepolyketide natural products [37], dihydroxerulic and xerulinic acid [38], bipinnatin J [39], elipticine [40], (+)-7-deoxytrans-dihydronarciclasine [41], gambierol [42], taiwaniaquinol [43], (−)-scabronine G [44], garsubellin A [45], piericidin A1 and B1 [46], lucilactaene [47], fostriecin [48], lupine alkaloids [49], ␤-C-glycosides [50], (+)-crocacin D [51], lobatamide analogs [52], epoxyquinoid compounds [53,54], (+)-SCH 351448 [55], 3-methyl-2,5-dihydro-1-benzoxepin carboxylic acids [56], (+)-ochromycinone and (+)-rubiginone B 2 [57], EI-1941-1 and EI-1941-2 [58], mycothiazole [59], 6 -epiperidinin [60], aureothin and N-acylaureothamine [61], cyercene A and placidenes [62], herbindole B [63], (+)-tubelactomicin A [64], saudin [65], peroxyacarnoates A and D [66], aureothin, N-acetylaureothamine, aureonitrile [67], elysiapyrones [68], altromycin B [69], (+)-phorboxazole A and analogues [70,71], (−)-SNF4435 C and (+)-SNF4435 D [72], A2E [73], paracentrone [74]<...>…”
Section: Carbon-carbon Bond-forming Reactions Via Transmetallationmentioning
confidence: 99%
“…154 The same species, P. ocellatus, provided the possibly artefactual peroxy derivative 279, 155 whose relative configuration was confirmed at the same year. 156 A Panamanian collection of the sacoglossan mollusc Elysia diomedea yielded the endoperoxide 280, structurally closely related to 279. 157 The observation of rearrangement of 280 with triethylamine to yield the known vicinal diexpoxide elysiapyrone A 158 prompted speculation of the biosynthetic intermediate of 280, likely to be in turn derived from a putative polypropionate alkenyl chaincontaining precursor reacting with singlet oxygen.…”
mentioning
confidence: 99%
“…The biomimetic synthesis of 9,10-deoxytridachione (15) was independently achieved by Baldwin et al [29] and Trauner et al [30]. Both research groups utilized a convergent cross-coupling approach to assemble the (2E,4Z,6E,8E)-polyene-pyrone 18, which was perfectly set up to undergo a 6π disrotatory electrocyclization to give the target cyclohexadiene 15.…”
Section: Tridachione Familymentioning
confidence: 99%
“…The powerful sequence involving double bond isomerization followed by electrocyclization cascades has been further developed by the research groups of Baldwin [29] and Trauner [30] in their syntheses of the molluscan polypropionate ocellapyrone A (27) [33]. Although the original synthetic target of both groups was 9,10-deoxytridachione (15) (Scheme 16.9), the key (2E,4Z,6E,8E)-tetraene 18 arrived at by both research groups was found to undergo further double bond isomerization to give the (2E,4Z,6Z,8E)-polyene 29.…”
Section: Ocellapyronesmentioning
confidence: 99%
See 1 more Smart Citation